PENGUATAN KURIKULUM PENDIDIKAN ANAK USIA DINI BERBASIS HINDU DI TAMAN KANAK-KANAK DESA ADAT TAMBAWU, KECAMATAN DENPASAR TIMUR, KOTA DENPASAR - Made Sukrawati; W.A Sindu Gitananda; Komang Agus Triadi Kiswara; I Gede Agus Darma Putra; I Kadek Sumadiyasa; Made Sudarsana; A.A Putra Dwipayana (JURNAL SEWAKA BHAKTI, 2022)
Education is a conscious effort made by educators to the students with the aim to change behavior that leads to positive. Likewise in early childhood education where students are expected to develop abilities and shape the character and civilization of a dignified nation in the context of educating the nation's life, aiming to develop the potential of students to become human beings who believe and fear God Almighty, have good morals and are healthy. knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. In order to answer this, teachers should be expected to be able to instill the values ??of Hindu religious education in every lesson carried out in early childhood education. The bottom line is how to develop a curriculum based on Hinduism. Based on the results of surveys and research conducted, it was known that early childhood education teachers at Tembau Kindergarten, Penatih District, East Denpasar, need to get a workshop related to strengthening the Hindu religion-based curriculum. The methods used in this activity are mentoring methods, practice, discussion methods, sustainability and evaluation.